The Expanding Field of Secondary Antibody Deficiency: Causes, Diagnosis, and Management - Patel, Smita Y.; Carbone, Javier; Jolles, Stephen (Frontiers in Immunology, 2019)
Antibody deficiency or hypogammaglobulinemia can have primary or secondary etiologies. Primary antibody deficiency (PAD) is the result of intrinsic genetic defects, whereas secondary antibody deficiency may arise as a consequence of underlying conditions or medication use. On a global level, malnutrition, HIV, and malaria are major causes of secondary immunodeficiency. In this review we consider secondary antibody deficiency, for which common causes include hematological malignancies, such as chronic lymphocytic leukemia or multiple myeloma, and their treatment, protein-losing states, and side effects of a number of immunosuppressive agents and procedures involved in solid organ transplantation. Secondary antibody deficiency is not only much more common than PAD, but is also being increasingly recognized with the wider and more prolonged use of a growing list of agents targeting B cells. SAD may thus present to a broad range of specialties and is associated with an increased risk of infection. Early diagnosis and intervention is key to avoiding morbidity and mortality. Optimizing treatment requires careful clinical and laboratory assessment and may involve close monitoring of risk parameters, vaccination, antibiotic strategies, and in some patients, immunoglobulin replacement therapy (IgRT). This review discusses the rapidly evolving list of underlying causes of secondary antibody deficiency, specifically focusing on therapies targeting B cells, alongside recent advances in screening, biomarkers of risk for the development of secondary antibody deficiency, diagnosis, monitoring, and management.